Cell autonomous and nonautonomous requirements for Delltalike1 during early mouse retinal neurogenesis. Issue 6 (4th April 2016) - Riesenberg, Amy N.; Brown, Nadean L.
Abstract : Background: In the vertebrate retina, six neuronal and one glial cell class are produced from a common progenitor pool. During neurogenesis, adjacent retinal cells use Notch signaling to maintain a pool of progenitors by blocking particular cells from differentiating prematurely. In mice there are multiple Notch pathway ligands and receptors, but the role(s) of each paralogue during retinal histogenesis remains only partially defined.Results: Here we analyzed the cell autonomous and nonautonomous requirements for the Deltalike1 ( Dll1 ) ligand during prenatal retinogenesis. We used the α‐Cre driver to simultaneously delete a Dll1 conditional allele and activate the Z/EG reporter, then quantified Dll1 mutant phenotypes within and outside of this α‐Cre GFP‐marked lineage. We found that Dll1 activity is required for Hes1 expression, both autonomously and nonautonomously, but were surprised that retinal ganglion cell differentiation is only blocked cell autonomously. Moreover, Dll1 does not act during cone photoreceptor neurogenesis. Finally, Dll1 mutant adult retinas contained small retinal rosettes and RGC patterning defects but were otherwise normal.Conclusions: Although Dll1 participates in bidirectional (cis + trans) Notch signaling to regulate Hes1 expression, it only acts cell autonomously (in cis) to interpret inhibitory signals from other cells that block RGC neurogenesis. Developmental Dynamics 245:631–640, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: Retinal progenitors require Dll1 both in cis and trans RGC neurogenesis requires Dll1 in cis. Dll1 does not regulate cone photoreceptor development.